No impact of sports practice before or after atrial fibrillation ablation on procedure efficacy in athletes: a case–control study. Issue 12 (22nd August 2019) - Decroocq, Marie; Ninni, Sandro; Klein, Cédric; Machuron, François; Verbrugge, Eric; Klug, Didier; Brigadeau, François; Lacroix, Dominique
Abstract: Aims: Limited data exist on the efficacy of catheter ablation (CA) for sport-related atrial fibrillation (AF). Impact of sports practice resumption post-CA remains unknown. We aimed to determine AF CA efficacy in athletes vs. non-athletes, and to assess the impact of sport practice resumption. Methods and results: From 1153 first-time AF CA performed between 2009 and 2017, 73 athletes were matched with 73 sedentary patients based on age, sex, and closest CA procedure date. Athletes were defined as performing ≥6 h/week of vigorous sports to achieve ≥2000 h accumulated lifetime sports activity. They were mostly males (93.2%) with a mean age of 55 ± 9.8 years. Before CA, athletes practiced 10.2 ± 3.9 h/week of vigorous exercise vs. 4.6 ± 3.4 after CA. Within first year after CA, physical activity was stopped in 12 (16.4%) athletes, lowered in 45 (61.9%), and resumed at same intensity in 16 (21.9%). Athletes and non-athletes suffered from same AF recurrence rates during 5-year follow-up after CA: 38 (52.0%) vs. 35 (47.9%), respectively [adjusted hazard ratio (HR) on age, body mass index (BMI), obstructive sleep apnoea (OSA), and reduced left ventricular ejection fraction (LVEF), 1.17 (0.70–1.97, P  = 0.54)]. No significant impact of physical activity resumption status was found regarding AF recurrence rates at 1-year and beyond ( P  = 0.60). Procedure effectiveness was significantly lower in athletes with non-paroxysmal AF [adjusted on age, BMI, reduced LVEF, and OSA HR 2.36 (confidence interval 1.19–4.70), P  = 0.01]. Conclusion: Sports practice before and after CA has no significant impact on AF recurrence rates in athletes within 5-year after AF CA.